Convective boundary layer flow of MHD tangent hyperbolic nanofluid over stratified sheet with chemical reaction - Alhefthi, Reem K.; Shahzadi, Irum; Khan, Husna A.; Khan, Nargis; Hashmi, M. S.; İnç, Mustafa (Amer Inst Mathematical Sciences-Aims, 2024)
We investigated the combined impact of convective boundary conditions, thermal conductivity, and magnetohydrodynamic on the flow of a tangent hyperbolic nanofluid across the stratified surface. Furthermore, the ramifications of Brownian motion, thermophoresis, and activation energy were considered. Heat generation, chemical reactions, mixed convection, thermal conductivity, and other elements were considered when analyzing heat transfer phenomena. The governing equations were converted via similarity transformations into non-dimensional ordinary differential equations in order to analyze the system. Using the shooting method, the problem's solution was determined. We showed the mathematical significance of the temperature, concentration profiles, and velocity of each fluid parameter. These profiles were thoroughly described and shown graphically. The findings demonstrated that as the Weissenberg number and magnetic number increased, the fluid velocity profile decreased. Higher heat generation and thermophoresis parameters resulted in an increase in the temperature profile. Higher Brownian motion and Schmidt parameter values resulted in a drop in the concentration profile. Tables were used to discuss the numerical values of skin friction (C-fx), Nusselt number (Nu(x)), and Sherwood number (Sh(x)). For the greater values of Weissenberg number and mixed convection parameters, skin friction numerical values fell while Nusselt numbers rose.
Keywords: Buongiorno nanofluid model; tangent hyperbolic nanofluid; heat generation; mixed convection; activation energy; stratified sheet